PROSPEK PENGEMBANGAN TANAMAN DAUN BAWANG (Allium porum L.) DI KELURAHAN LANDASAN ULIN KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Ahmad Baparki (Chlorophyl, 2024)
The prospect of developing spring onion (allium porum l.) plants in Landasan Ulin Village, Liang Anggang District, Banjarbaru City, South Kalimantan Province”. This research was conducted on Jalan Sumber Murni, Landasan Ulin Utara Village, Liang Anggang District, Banjarbaru City, South Kalimantan Province. The average production is 462 kg/farmer, with the prevailing price of Rp. 15,000/kg, the average income of spring onion farmers is Rp. 6,975,000/farmer. The average income obtained by farmers in one harvest season is Rp. 2,586,781.85 per farmer